PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBASIS GOOGLE SITES PADA MATA PELAJARAN IPA KELAS VI SEKOLAH DASAR NEGERI 008 LOA JANAN ILIR - Rahmanudin, Rahmanudin; Yudha Saputra, Galih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Google Sites-based digital learning media for sixth-grade science learning at SDN 008 Loa Janan Ilir. This research used a Research and Development (R&D) method with the 4D development model consisting of define, design, develop, and disseminate stages. The research subjects included a material expert, media experts, and 25 sixth-grade students. Data were collected through observation, interviews, expert validation questionnaires, and student response questionnaires. The results showed that the developed learning media was categorized as very feasible based on the material expert validation score of 70 and the media expert validation average score of 68.67. The limited trial results also showed very positive student responses with an average score of 64.44 in the very feasible category. Therefore, the Google Sites-based digital learning media is suitable to be used as a supporting learning media for science learning in elementary schools.